Lo humano y lo trágico en Schiller y Goethe: The Human and the Tragic in Schiller and Goethe - Salmerón Infante, Miguel (Universidad del Zulia, 2021)
Schiller and Goethe maintained a close friendship that allowed them to deal with anthropological, literary and aesthetic questions. Schiller (reader of Kant) was poured towards the interior and Goethe (natural researcher) towards the exteriority. Another possible difference is in their visions of the inevitable. In Schiller the Antigone model prevailed (the fatal derives from objective political conflicts). In Goethe the Oedipus model would have validity (the fatal is attributable to the designs of destiny). This made actions predominate in Schiller's tragedies and characters in Goethe's.